Dynamic Analysis of UPLC-MS/MS for Sugar and Organic Acid Components of Pears with Different Flesh Texture Types During Development - Chen Yin; Luming Tian; Jing Li; Yufen Cao; Xingguang Dong; Ying Zhang; Dan Qi (Agronomy)
Pears are popular among consumers for their juicy and delicious taste. In this study, the sugar and organic acid compositions of pear fruits with different texture types during development were determined by ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS), and fruit texture traits were determined by a texture analyzer. The results showed that the dominant sugar in soft and crispy types of pear fruits was fructose. The main difference between pears was the second-highest sugar component; glucose content was higher in crispy-flesh pear fruits while sucrose content was higher in soft-flesh pear fruits. The composition of organic acid components in both texture types of pear fruits was similar. The turning points of changes in the content of sucrose, sorbitol, glucose and quinic acid were different between different-textured pear varieties. A Pearson correlation analysis showed that sugar and organic acid components were significantly correlated with single fruit weight and soluble solid contents (SSCs), respectively. There was a high correlation among texture traits, individual sugars and organic acids. A partial least squares discriminant analysis (PLS-DA) VIP score plot showed that the differential traits with scores greater than 1 were total soluble sugars/total organic acids (TSSs/TAs), fracture and malic acid/citric acid (MA/CA), which could distinguish pear fruits of different texture types better and reflect the uneven quality differences among pear fruits adapted to different origins. The comprehensive analysis results of the flesh texture parameters and sugar and organic acid components are in line with objective reality and will provide a reference for quantitative indicators of the sensory evaluation of pear varieties as well as for molecular mechanism research on trait differences.